The Effect of Modification of Passing Down to the Wall Exercise on the Improvement of Underpass Skills in Volleyball Game Club Galaxy Suban Baru - Ayu Zila Meranti; Ilham Arvan Junaidi; Agung Mahendra (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The problem in this study is the underpass in the new Seban Galaxy club volleyball game which is still not good and correct due to the lack of varied underpass training methods. The purpose of this study was to determine whether there was an effect of the downward to the wall passing modification exercise on increasing the ability to pass under the club galaxy suban baru. This type of research is an experiment. The population in this study amounted to 20 people. The sampling technique in this study used a total sampling technique, the sample in this study consisted of 20 players. The data collection technique used the lower passing ability test. The data analysis technique uses the t-test formula with a significance level of 0.05%. Based on the results of research that has been conducted on club volleyball players in the new Galaxy Suban, the average pretest result is 14.8 and the post-test average is 18.05. From the results of the t-test, it can be seen that t count t table with t count of 2.912 and t table 2.028 (df 19) so that it can be concluded that there is a significant effect on passing drills down to the wall towards improving the ability to pass under the new suban galaxy club.